Stability of Gut Enterotypes in Korean Monozygotic Twins and Their Association with Biomarkers and Diet - Lim, Mi Young (Sci Rep, 2014)
Studies on the human gut microbiota have suggested that human individuals could be categorized into enterotypes based on the compositions of their gut microbial communities. Here, we report that the gut microbiota of healthy Koreans are clustered into two enterotypes, dominated by either Bacteroides (enterotype 1) or Prevotella (enterotype 2). More than 72% of the paired fecal samples from monozygotic twin pairs were assigned to the same enterotype. Our longitudinal analysis of these twins indicated that more than 80% of the individuals belonged to the same enterotype after about a 2-year interval. Microbial functions based on KEGG pathways were also divided into two clusters. For enterotype 2, 100% of the samples belonged to the same functional cluster, while for enterotype 1, approximately half of the samples belonged to each functional cluster. Enterotype 2 was significantly associated with long-term dietary habits that were high in dietary fiber, various vitamins, and minerals. Among anthropometrical and biochemical traits, the level of serum uric acid was associated with enterotype. These results suggest that host genetics as well as host properties such as long-term dietary patterns and a particular clinical biomarker could be important contributors to the enterotype of an individual.